2014
DOI: 10.1504/ijtm.2014.064018
|View full text |Cite
|
Sign up to set email alerts
|

Proximity, knowledge transfer, and innovation in technology-based mergers and acquisitions

Abstract: This paper presents the findings from a qualitative study on the extent to which three dimensions of proximity -geographic, cognitive, and organisational -impact knowledge transfer and innovation post-merger and acquisition (M&A). Findings show that the elements of proximity substantially influence both knowledge transfer and innovation although the nature of the impact varies and is influenced by the type of management interventions or lack thereof post-M&A.Keywords: proximity; knowledge transfer; mergers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 58 publications
0
16
0
1
Order By: Relevance
“…Ebből következik, hogy a perifériákon is működhet innováció -még ha az rejtett vagy lassú is. Különösen akkor, ha a periféria vállalata közelinek tekinthető − nem zikai, hanem kognitív, szervezeti, kulturális vagy technológiai értelemben − a távoli központok vállalataihoz (Ensign et al 2014).…”
Section: Globális-lokális Viszonyok a 21 Század Elejénunclassified
“…Ebből következik, hogy a perifériákon is működhet innováció -még ha az rejtett vagy lassú is. Különösen akkor, ha a periféria vállalata közelinek tekinthető − nem zikai, hanem kognitív, szervezeti, kulturális vagy technológiai értelemben − a távoli központok vállalataihoz (Ensign et al 2014).…”
Section: Globális-lokális Viszonyok a 21 Század Elejénunclassified
“…Geographical proximity can facilitate the success of a transaction through the ease of transmitting information about the future investments (Sorenson & Stuart, 2001). In addition, the information is more accurate when the companies are close to each other and the flow is direct (Ensign et al, 2014;Uysal et al, 2008).…”
Section: Related Studiesmentioning
confidence: 99%
“…If two companies are in proximity, then there is a significant chance that they know each other well, what facilities they have, if the human capital is qualified or if the company is highly profitable. In other words an increase in the distance between the acquiring and the potential target reduces the chance of knowing each other and so reduces the likelihood of a merger between companies (Ensign, Lin, Chreim, & Persaud, 2014;Uysal, Kedia, & KEYWORDS takeover bids; geographical proximity; m&a decision; probability of success Panchapagesan, 2008). This finding was first noticed in the domestic M&As in the banking industry (DeLong, 2001;Houston, James, & Ryngaert, 2001), but there are studies that have concluded that cross-country transactions have the same trend (Eckbo & Thorburn, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…M&A-induced innovation synergies are mainly a form of the so-called operational synergies, different from, for example, collusion-based or financial synergies (Chatterjee 1986;Larsson and Finkelstein 1999). Operational synergies require a certain level of integration in functional areas, and resources and capabilities must, to a certain extent, be transferred (Haspeslagh and Jemison 1991;Ensign et al 2014). For practical reasons we include in the study managerial synergies, which are the result of replacing resources or recombining capabilities (Larsson and Finkelstein 1999).…”
Section: Manda Innovation Synergiesmentioning
confidence: 99%
“…Companies that aim for structural linkages deploy a variety of instruments, ranging from social events, liaison offices, cross-company project groups, integration managers, up to fully integrated departments (Gerpott 1995;Birkinshaw, Bresman, and Hakanson 2000;Ranft and Lord 2002;Teerikangas, Very, and Pisano 2011). This integration mechanism may reduce resistance to change, the impact of alliances and pre-M&A routines, culture clashes, retain key employees, stimulate the transfer and integration of tacit knowledge, and promote the adaptation of cultures routines (Birkinshaw, Bresman, and Hakanson 2000;Epstein 2004;Agarwal et al 2012;Heimeriks, Schijven, and Gates 2012;Ensign et al 2014;Sabidussi et al 2014).…”
Section: Pmai Mechanismsmentioning
confidence: 99%